The Education of Love and its Relevance to Islam as a Religion of Compassion: A Study on the Concept of Mahabbah of Rabi’ah al-Adawiyah - Amir Maliki Abitolkha; Muhamad Basyrul Muvid (Religio: Jurnal Studi Agama-agama, 2021)
The concept of love defined by Rabi’ah Al-Adawiyah, known as mahabbah, is a situation where love is not meant except for Allah. No one is remembered, longed for, and loved except Him. Love for Him is a representation of the process of riyādah and mujāhadah. Education of love in the concept of mahabbah is an effort to guide, shape, and educate a servant to become a person who has noble character and has a high spiritual soul to Allah. The relevance of education of love to Islam as a religion of compassion (rahmah) is the goal to fight hatred, envy, enmity, tension, social jealousy, violence, differences, and disputes. All of this is replaced by a sense of love, peace, and harmony among creatures, in the sphere of religion, state, and world. In particular, this article will examine 1) the concept of Rabi’ah Al-Adawiyah’s mahabbah, 2) the education of love in the Sufistic dimension of Rabi'ah Al-Adawiyah, and 3) the relevance of love education in the Sufistic dimension of the mahabbah towards Islam as a religion of compassion.